Nari's strategic alignment in entering indonesia power development project - Dong, Lili; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2018)
Abstract. This paper explores the marketing issues in order to propose a feasible marketing strategy in promoting NARI’s sustainable market development in Indonesia.  In the analyses, SWOT and PESTL are used to identify and analyze the macro and micro environment of NARI’s market opportunity and conducted a comprehensive review on the market environment that may affect NARI’s core business, such that the issues can be clearly identified and recommended solution to resolve the issues can be formulated. The analysis based on the marketing condition of NARI, the marketing model is developed with a systematic mapping tailored to NARI’s brand strategy, product strategy, project strategy, management strategy and development strategy.  The strategy analysis and evaluation suggested NARI to conduct a in depth and comprehensive analysis of Indonesia's electricity power market and grab the business opportunities. In current fierce and quick changing market environment, NARI needs to increase its market share by applying the innovative marketing strategy and build strong brand to meet customer expectation.Key word: Marketing, NARI, PESTL, Strategy, SWOT